CONNOTATIVE AND DENOTATIVE MEANING ANALYSIS OF VERBAL SIGN IN OLAY ADVERTISEMENT - Melita Arista Sulas (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This study concerns to find out the connotative and denotative meaning of the verbal sign in Olay advertisement. The data of this study were taken from Olay advertisement that were collected from online advertisement. The data of this study were analyzed by using descriptive qualitative method. This study used the theory of signs proposed by Chandler (2001: 28) to find out the verbal sign and theory of meaning proposed by Barthes (1967) to find out the meaning of verbal sign in Olay advertisement. Through the analysis, it is found that verbal sign has important rules to make an attractive advertisement. The verbal sign contais connotative and denotative meaning. In this study, the researcher found connotative meaning in Olay advertisement that has hidden meaning and denotative meaning that has literal meaning to convey the messages of Olay advertisement. The result found denotative meaning more dominant than connotative meaning because the advertisements used more literal meanings rather than hidden meaning to convey the messages toward the viewers.